SUPERVISI KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU DALAM PEMBELAJARAN ABAD 21 - Hary Nur Syamsuddin; Desy Tri Ferawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Teachers as professionals will need continuous and continuous coaching, and make teachers as laborers need to be considered, valued and recognized for their professionalism. To make them professional, not only improve their competence, increase discipline, provide motivation, provide guidance through supervision, provide incentives, and pay a decent salary to their professionals to enable teachers to be satisfied in working as educators. One of the factors that becomes a benchmark for school success is the teacher's performance in teaching in supervision. Principals as supervisors in the world of education have an important role in fostering, aimed at improving the quality of teaching, knowledge, motivation and improving the quality of teachers in carrying out their duties, especially now that 21st century learning-based learning requires teachers to be more professional, not only can teaching in the learning process but also must be able to master various modern technological tools and supporting technological means in educational activities.